Understanding history for grade 8 book 3 - Riaz, Ismat (Karachi, Pakistan Oxford university press, 2023)
The series explores the critical historical and geographical roles of the region Pakistan lies in through the ages. It follows the path of history by introducing the earliest civilisations to the rise of the Islamic civilisation and its interaction with its European counterparts in Book 1 for grade 6. Book 2 for grade 7 explores the Medieval Ages and the impact of Islamic empires and the Crusades. It carries the subcontinent$1 (Bs history forward from the founding of the Delhi Sultanate to the rise, peak, and decline of the Mughals. Book 3 for grade 8 covers the struggle of Indians against foreign domination, the rise of the British East India Company and its transition to the British Raj in the subcontinent, the role of personalities, both saints and leaders of the Pakistan Movement that led to the creation of Pakistan, and significant events in Pakistan since 1947. It also covers the impact of meaningful world events, such as the two World Wars and the Cold War, that directly or indirectly affected Pakistan.s
Keywords: Oxford history